Monocyte-driven atypical cytokine storm and aberrant neutrophil activation as key mediators of COVID-19 disease severity - L. Vanderbeke (Nature Portfolio, 2021)
The host immune response plays a critical role in the immunopathology of SARS-CoV2. Here the authors combine a systems biology approach to implicate monocytes as key drivers of cytokine storm and disturbed neutrophil activation in COVID-19 disease severity.